α-Defensins Promote Bacteroides Colonization on Mucosal Reservoir to Prevent Antibiotic-Induced Dysbiosis - Ou, Jiayao; Liang, Shaonan; Guo, Xue-Kun; Hu, Xiaoyu (Frontiers in Immunology, 2020)
In addition to their established functions in host defense, accumulating evidence has suggested an emerging role for anti-microbial proteins (AMPs) in shaping commensal microbiome. However, the role of α-defensins, the most abundant AMPs of intestine, in regulating microbial ecology remains inconclusive. Here, experiments utilizing mice deficient in matrix metalloproteinase 7 (MMP7), the α-defensin-activating enzyme, with rigorous littermate controls showed that α-defensin deficiency did not significantly influence steady-state intestinal microbiota. In contrast to their dispensable role in homeostasis, α-defensins are essential for replenishment of commensal Bacteroides from the mucosal reservoir following antibiotics-induced dysbiosis, shown by markedly compromised recovery of Bacteroides in Mmp7-/- animals. Mechanistically, α-defensins promote Bacteroides colonization on epithelial surfaces in vivo and adhesion to epithelial cells in vitro. Moreover, α-defensins unexpectedly does not show any microbicidal activities against Bacteroides. Together, we propose that α-defensins promote commensal bacterial colonization and recovery to maintain microbial diversity upon environmental challenges.